Effect of Combination Intake of Protein, Vitamin C, and Blood Boost Tablets on Hemoglobin Levels of Adolescent Girls: Pengaruh Kombinasi Asupan Protein, Vitamin C dan Tablet Tambah Darah terhadap Kadar Hemoglobin Remaja Putri - Kusdalinah Kusdalinah; Desri Suryani; Arie Nugroho; Yunita Yunita (Universitas Airlangga, 2023)
Anemia occurs when the blood hemoglobin concentration is lower than normal due to a deficiency of one or more nutrients. The impact of anemia on young women is decreased work productivity, stunted growth, more susceptible to infection, reduced body fitness, decreased enthusiasm for learning and decreased achievement The aim of this study was to determine the effect of a combination of intake of protein, vitamin C and blood supplement tablets on hemoglobin levels of young women in Bengkulu. This type of experimental research. The research design is pre-experimental. The statistical test used is the paired t-test. The average protein intake is 64.03 grams, the standard deviation is 1.13. The average intake of vitamin C is 100.5 mg, the standard deviation is 1.91. The mean intake of iron is 66.9 mg, the standard deviation is 1.65. While the average Hb level before treatment was 11.01 g/L, a standard deviation of 1.06 g/L, while the average Hb level after treatment was 13.60 g/L, a standard deviation of 2.63 g/L. P value = 0.0005 which means significant. There was a significant effect of the treatment of giving a combination of protein intake, vitamin C and blood boost tablets consumed by female students for 14 days of treatment on the increase in hemoglobin levels. It is hoped that further research can modify the research design, namely a quasi-experimental design.